Czech-Slovak Conference Minority Memoryscapes. Competitive Societies of Memory? June 10-11, 2010, Prague, Czech Republic. - Pauknerová, Karolína (Lidé města, 2010)
The "Minority Memoryscapes. Competitive Societies of Memory?" conference organized by the Faculty of Humanities, Charles University in Prague and the Jewish Museum of Prague, took place in Prague on the premises of the Jewish Museum on June 10-11, 2010. Blanka Soukupová, Zuzana Jurková, and Hedvika Novotná were the chief conference organizers. Costs of the conference were covered from a Charles University Special Research project called "Postmodern Society - Memory - Culture - Identity".